Maximal aerobic speed as prior reference point skills fitness capacities among elite male volleyball players - M. Zerf; L. Louglaib (Physical Education of Students, 2019)
Purpose . Maximal aerobic speed (MAS) levels are a prior reference point in the optimal management of effort parameters motor skills-related fitness. Typically indicated in sports literariness by improving the aerobic components that work to develop muscle flexibility, coordination of joint movements, the increase of speed and strength, which their developments advance the overall physical condition of the players. Methods . To solve the objective of this research, we establish the MAS levels of 60 elite male volleyball players (aged 22 to 25 years, ±5 years in elite championships). As well as their motor skill-related fitness, inspected by 20m speed, T-test agility and power strength volleyball test jumps (vertical or horizontal). Results . Our results confirm maximal aerobic speed (MAS) values as essential components for the player to achieve high performance under high explosive loads. Upkeep by our protocol to be advanced at MSA upper than 3.99 (m/s). Suspected as a variation of effort energy consumption. Explained by similarity through different resistance player capacities relative to its biomechanical particular gesture activity improvements or its movement technique optimized to his boundary conditions. Conclusions . Our protocol supports MAS levels (MAS) as an excellent test to evaluate the development of motor abilities in masculine volleyball. Upkeep by our protocol to be developed at MSA +3.99 (m/s). Claims as a minimal component of the conditioning to improve the motor volleyball skill-fitness ability. Subjected in this study as an easy volleyball-test tool to predict players' speed, agility, coordination and power developments. Challenging our trainers to access the player's anaerobic energy as a pointer of players’ physical capacity skills fitness progress.